German-Language Feminist Exegesis of the Pauline Letters: a Survey - Sutter Rehmann, Luzia 1960- (2001)
German-language feminist exegesis devotes much energy to a critique of the concept of the 'historical Paul'. More is involved than supplementary insights from a female point of view, or a reduced feminism that would concentrate on Paul and his relationship to women: rather, it is the entire pattern of interpretation that must be changed. The history of interpretation has overlooked women's reality; this has gone hand in hand with a refusal to perceive Jewish reality. The starting point for feminist exegesis is the perception of the context of the letters as a relational network which generates questions; Paul cannot be detached from this network. The attempt is made to bring out clearly those passages in his letters where emancipation breaks through, and to keep these passages open.